Different brain activation patterns in the prefrontal area between self‐paced and high‐speed driving tasks. Issue 6 (23rd February 2022) - Hirano, Daisuke; Kimura, Naotoshi; Yano, Hana; Enoki, Miku; Aikawa, Maya; Goto, Yoshinobu; Taniguchi, Takamichi
Abstract: The purpose of this study was to investigate the effects on prefrontal cortex brain activity when participants attempted to stop a car accurately at a stop line when driving at different speeds using functional near‐infrared spectroscopy (fNIRS). Twenty healthy subjects with driving experience drove their own cars for a distance of 60 m five times each at their own pace or as fast as possible. The variation in the distance between the stop line and the car was not significantly different between the self‐paced and high‐speed tasks. However, oxygenated hemoglobin concentration in the prefrontal cortex was significantly higher in the high‐speed task than in the self‐paced task. These findings suggest that driving at high speed requires more divided attention than driving at self‐paced speed, even though the participants were able to stop the car at the same distance from the target. This study shows the advantages and usefulness of fNIRS . Abstract : Monitoring brain activity with functional near‐infrared spectroscopy can be useful in real driving situations. We examined the differences in prefrontal cortex activity when participants attempted to stop a car accurately at a stop line when driving at different speeds. Oxygenated hemoglobin concentration in the prefrontal cortex was significantly higher in the high‐speed task than in the self‐paced task, although the variation in the distance between the stop line and the car was not significantly different between both tasks.